1989
DOI: 10.1172/jci114376
|View full text |Cite
|
Sign up to set email alerts
|

Detection of three distinct patterns of T helper cell dysfunction in asymptomatic, human immunodeficiency virus-seropositive patients. Independence of CD4+ cell numbers and clinical staging.

Abstract: We have tested the T helper cell (TH ) potential of asymptomatic, HIV seropositive (HIV+) patients, using an in vitro assay for IL-2 production. Peripheral blood leukocytes (PBL) from 74 HIV+ patients and 70 HIV-control donors were tested for TH function when stimulated with influenza A virus (FLU), tetanus toxoid (TET), HLA alloantigens (ALLO), or PHA. Of the HIV+ patients, four different response patterns were observed: (a) patients who responded to all four stimuli (16%); (b) patients who were selectively u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
343
0
2

Year Published

1994
1994
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 606 publications
(364 citation statements)
references
References 29 publications
17
343
0
2
Order By: Relevance
“…Cytokine and cytokine receptor determination IL-2 activity in SN was assessed as the ability to stimulate the proliferation of the IL-2-dependent mouse cell line, CTLL, as described [10]. Briefly, 1 2 10 4 CTLL/well and three-fold successive dilutions of SN were cultured for 24 h, pulsed with 1 Ci of 3 H-thymidine (Rotem Industries Ltd, Nuclear Research CenterNegev, Israel) and harvested 18 h later.…”
Section: Cell Culture Supernatant Preparationmentioning
confidence: 99%
“…Cytokine and cytokine receptor determination IL-2 activity in SN was assessed as the ability to stimulate the proliferation of the IL-2-dependent mouse cell line, CTLL, as described [10]. Briefly, 1 2 10 4 CTLL/well and three-fold successive dilutions of SN were cultured for 24 h, pulsed with 1 Ci of 3 H-thymidine (Rotem Industries Ltd, Nuclear Research CenterNegev, Israel) and harvested 18 h later.…”
Section: Cell Culture Supernatant Preparationmentioning
confidence: 99%
“…Such a mechanism may explain the gradual progressive CD4 T cell depletion observed in HIV-infected individuals, since cells should only be deleted upon encountering their specific antigen; no cell deletion would occur without specific activation. This mechanism would also explain the progressive proliferative defect in response to recall antigens observed in asymptomatic HIV-infected individuals [1][2][3]. The fact that deletion occurs only after the encounter with activating antigens is illustrated in a study comparing the proliferative response of T cells from normal control or HIV-infected individuals with fractionated cytomegalovirus (CMV) antigen.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major and specific features of the HIV infection physiopathology, detected as early as seroconversion [9] before any CD4 T cell loss, is the selective failure of CD4 T cells to proliferate in vitro in response to recall antigens [1][2][3] or to superantigens [4,7], whereas their proliferative response to polyclonal mitogens is maintained [1,2,5,6]. We and others have shown that this proliferative defect after activation of peripheral blood mononuclear cells (PBMC) from HIV-infected individuals with either superantigens [4,7] or recall antigens (G. Shearer, personal communication) correlates with specific induction of CD4 T cell death.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The progression of HIV infection is also characterized by a complex dysregulation in the function of TH cells (Lane et al, 1985;Giorgi et al, 1987;Miedema et al, 1988;Clerici et al, 1989). At least two different types of functional defects have been observed in HIV-infected individuals.…”
Section: Cell Mediated Immunity Is Defective In Hiv Infectionmentioning
confidence: 99%